Proving the Elements of Fault in the Accountability of the Perpetrator of the Crime of Premeditated Murder - Rochyana, Amir Rachman; Pratiwi, Siswantari; Mardani, Mardani (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
The judicial process without primair evidence of the defendant Jessica Kumala alias Jessica Kumala Wongso alias Jess can be sentenced to criminal punishment by tracing a person's motive for committing a criminal offense that results in the loss of life of another person must be responsible for his actions as regulated by Article 340 of the Criminal Code. Normative juridical research using the deductive thinking method of objects analyzed with a qualitative approach, the research refers to the legal norms contained in the legislation. The basis of consideration of the Panel of Judges in imposing punishment on the defendant of premeditated murder in the First Level Decision Number 777/Pid.B/2016/PN.Jkt.Pst. Judges have the right to accept or override the opinion of expert testimony, but it must be based on appropriate reasons, because in exercising their authority, judges must be truly responsible for the realization of truth and legal certainty. In terms of deciding a case, the judge's belief is very important. This is in accordance with the judge's decision in the Jessica case where the judge has his own view of the case where the judge's instinct is very important. The legal perspective on intentionality that results in the loss of life of others as the author has explained is that intent in criminal law is part of guilt. The intent of the perpetrator has a closer psychological connection to an act (which is prohibited) than negligence (culpa).